Theorising about child maltreatment: Narrative review on health education models, conceptual frameworks and the importance of the information and communication technologies - Gómez-Cantarino, Sagrario; Mazoteras-Pardo, Victoria; Rodríguez-Montejano, José; Gradellini, Cinzia; Cunha-Oliveira, Aliete; Ugarte-Gurrutxaga, María Idoia (Frontiers in Psychology, 2022)
Child maltreatment is conceived as a public health problem. Therefore, it is appropriate to analyse the explanatory models that deal with this behaviour, reflecting these postulates within the panorama of health education, which makes health professionals responsible for taking action. In order to do this, the theoretical context and the awareness of nursing students in relation to these theories must be analysed. In turn, the use of information and communication technologies (ICT) in this field should be valued, due to their capacity to manage and systematise information, becoming a relevant tool when training future nursing professionals. Without forgetting that health informatics is a spectrum of multidisciplinary fields that includes the study of the design, development and application of computational techniques to improve health care. A review of the scientific literature was carried out, for which primary and secondary sources were consulted, tracing a search for data thanks to the keywords: "nursing"; "abuse"; "children"; "education" and "theory". During the second half of the 20th century, several health paradigms have been developed, which present different pathways to health education. There have also been three generations of theoretical models that attempt to analyse the public health problem of child maltreatment. This reflects the need for a transdisciplinary approach to child abuse, where there is no one explanatory model that is more appropriate than another, but where the choice of the health education paradigm and, within this, the most recommendable theory will depend on each situation.